2020
DOI: 10.1093/nar/gkaa1066
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of endogenous and heterogeneous yeast terminators in Pichia pastoris to tune mRNA stability and gene expression

Abstract: In the yeast Saccharomyces cerevisiae, terminator sequences not only terminate transcription but also affect expression levels of the protein-encoded upstream of the terminator. The non-conventional yeast Pichia pastoris (syn. Komagataella phaffii) has frequently been used as a platform for metabolic engineering but knowledge regarding P. pastoris terminators is limited. To explore terminator sequences available to tune protein expression levels in P. pastoris, we created a ‘terminator catalog’ by testing 72 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 41 publications
(40 reference statements)
2
30
0
Order By: Relevance
“…This strain can be used for maximized production of other isoprenoid products including squalene ( Paradise et al, 2008 ; Ding et al, 2014 ). Ito et al (2020) showed tuneable gene expression in P. pastoris using endogenous terminators of S. cerevisiae ( Ito et al, 2020 ). Here, we also report the successful transferability of terminators and promoters, such as the CYC1 minimal promoter, from S. cerevisiae to P. pastoris ( Figure 5A ), in addition to plant-derived ATF/BSs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This strain can be used for maximized production of other isoprenoid products including squalene ( Paradise et al, 2008 ; Ding et al, 2014 ). Ito et al (2020) showed tuneable gene expression in P. pastoris using endogenous terminators of S. cerevisiae ( Ito et al, 2020 ). Here, we also report the successful transferability of terminators and promoters, such as the CYC1 minimal promoter, from S. cerevisiae to P. pastoris ( Figure 5A ), in addition to plant-derived ATF/BSs.…”
Section: Discussionmentioning
confidence: 99%
“…By employing only nine (three weak, three medium, and three strong) plant-derived ATFs and their corresponding BSs, we previously established a combinatorial library of S. cerevisiae variants that allow a wide range of gene expression fine-tuning ( Naseri et al, 2019 ). Considering the similarity between S. cerevisiae and P. pastoris , functional regulators of S. cerevisiae are expected to be transferable to P. pastoris ( Ito et al, 2020 ). A recent study showed that among the 72 terminators in S. cerevisiae , 41 had a high degree of transferability to P. pastoris ( Ito et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent work has shown that terminator sequences can be designed as tunable control elements that can be “turned on” to attenuate gene transcription at low temperatures ( Roßmanith et al, 2018 ). With the growing evidence that the structural components of terminators may be malleable depending on species, future work should focus on understanding the combined contributions of terminator components, including those beyond transcriptional control (e.g., modulation of protein expression) for metabolic engineering ( Curran et al, 2013 ; Ito et al, 2020 ). This may lead to better designs for strong synthetic terminators with consistent cross-species performance.…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al characterized 72 terminators derived from P. pastoris , S. cerevisiae , and synthetic terminators, and found that the tunable range could reach up to 17-fold. Interestingly, the S. cerevisiae terminators could maintain their function after being transferred to P. pastoris [ 61 ]. These preliminary studies indicated the significance of terminators in regulating the expression level of heterologous genes and more mechanistic studies should be carried out in the near future.…”
Section: Synthetic Biology Toolkit For P Pastorismentioning
confidence: 99%